2012
DOI: 10.1103/physrevc.85.035206
|View full text |Cite
|
Sign up to set email alerts
|

Momentum dependence of theφ-meson nuclear transparency

Abstract: The production of φ mesons in proton collisions with C, Cu, Ag, and Au targets has been studied via the φ → K + K − decay at an incident beam energy of 2.83 GeV using the ANKE detector system at COSY. For the first time, the momentum dependence of the nuclear transparency ratio, the in-medium φ width, and the differential cross section for φ-meson production at forward angles have been determined for these targets over the momentum range of 0.6-1.6 GeV/c. There are indications of a significant momentum depende… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 43 publications
4
45
0
Order By: Relevance
“…The φ production was also analyzed in proton-induced reactions off different nuclear targets by the ANKE collaboration. The p + A collisions at E beam = 2.83 GeV, with A = C, Cu, Ag, and Au, were measured at the COSY accelerator by the ANKE detector, and the final state φ → K + K − was studied [15]. The discussion of these results is presented in the next Sec.…”
Section: Experimental Detection Of φ In Nuclear Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…The φ production was also analyzed in proton-induced reactions off different nuclear targets by the ANKE collaboration. The p + A collisions at E beam = 2.83 GeV, with A = C, Cu, Ag, and Au, were measured at the COSY accelerator by the ANKE detector, and the final state φ → K + K − was studied [15]. The discussion of these results is presented in the next Sec.…”
Section: Experimental Detection Of φ In Nuclear Mattermentioning
confidence: 99%
“…The φ, in particular, is very narrow in vacuum and is well separated from the ρ and the ω mesons, allowing for the measurement of any modifications of its mass or width in matter. To that end, several experiments have been carried out, such for photoproduction [13,14], for proton-induced [15,16] and pion-induced [17] reactions, an effort that has been accompanied by important theoretical developments to understand the modifications of the φ meson in dense nuclear matter.…”
Section: Introductionmentioning
confidence: 99%
“…The ϕ production in nuclei has been intensively studied both experimentally [1][2][3][4], as well as in theoretical analyses [4][5][6][7][8]. The ϕ nuclear transparency ratio, measured in proton-induced and photoproduction experiments, points to a large absorption in nuclei, consistent with widths about one order of magnitude larger than the one from its dominant decay toKK in vacuum.…”
Section: Introductionmentioning
confidence: 95%
“…[3] widths of 23 − 100 MeV are reported, even for densities of only half the normal nuclear-matter density. Since the measurement of ϕ absorption with momentum binning has been made [4], theoretical calculations of the momentum dependence of the ϕ self-energy are also of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the φ production in nuclei was studied by the KEK-PS-E325 Collaboration [23], the LEPS Collaboration at Spring8/Osaka [24], the CLAS Collaboration at the Jefferson Lab [25], and very recently by the ANKE experiment at COSY-Jülich [27]. Together with theoretical predictions [26,27] on the nuclear transparency ratio it has been concluded that the φ experiences a huge absorption in nuclei, consistent with inelastic widths about one order of magnitude higher than its dominant decay in vacuum. These results point at medium effects typically larger than predicted by hadronic models, leaving room for additional interaction processes with the nuclear medium.…”
Section: Kn Interaction In Hot and Dense Nuclear Mattermentioning
confidence: 99%